Inter-cycle variability of anti-Müllerian hormone: implications for predicting controlled ovarian stimulation cycle outcomes - Yavuz Emre Şükür; Batuhan Aslan; Necati Berk Kaplan; Musa Doğru; Batuhan Özmen; Murat Sönmezer; Bülent Berker; Cem Somer Atabekoğlu; Ruşen Aytaç (BMC, 2024)
Abstract Background Anti-Müllerian hormone (AMH) is a widely used marker for estimating ovarian reserve, and it may predict response to ovarian stimulation. While AMH is considered a stable, cycle-independent marker, studies have shown it can exhibit significant fluctuations based on factors like age, reproductive stage, and menstrual cycle phase. The fluctuations in AMH levels can make it challenging to predict individual responses accurately, particularly when the AMH is not measured in the COS cycle. The aim of this study was to assess the inter-cycle variability of serum AMH levels in two consecutive menstrual cycles and their correlation with response to controlled ovarian stimulation outcome in the latter. Methods In this single-centre retrospective cohort study, data of normal and low responder patients who underwent intracytoplasmic sperm injection following a GnRH antagonist cycle at a university hospital infertility clinic between January 2022 and December 2023 were reviewed. Serum AMH levels were measured in the early follicular phase of two consecutive menstrual cycles with Elecsys-AMH Roche® system (Roche Diagnostics, Meylan, France). Correlations between AMH levels and controlled ovarian stimulation outcomes, including total oocyte and mature oocyte (MII) counts, were assessed. The study included normal and poor responder women to maintain data integrity. Results A total of 79 patients were included in the final analyses. Significant cycle-to-cycle variation in serum AMH levels was observed, with a median variation of 44.3%. Normal responders exhibited a mean change of 0.60 ± 0.46 ng/ml, while poor responders had a mean change of 0.28 ± 0.28 ng/ml. Approximately 20% of patients were reclassified between normal and poor responder categories based on the second AMH measurement. The controlled ovarian stimulation cycle AMH levels showed a stronger correlation with both total oocyte count (r = 0.871, P < 0.001) and MII oocyte count (r = 0.820, P < 0.001) compared to preceding cycle AMH levels. Conclusion AMH levels can exhibit significant variations between consecutive cycles, potentially leading to misclassification of patients. Measuring AMH in the early follicular phase of the COS cycle provides a more accurate prediction of the numbers of total and MII oocytes collected. Consistent and repeated AMH measurements can help clinical decision-making.